The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1159/000508706
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Distress and Associated Factors in Patients with Diabetes Mellitus in South East Nigeria

Abstract: Background: Diabetes distress (DD) is a common worldwide problem in diabetic patients irrespective of age and type of treatment. In the DAWN 2 study (Diabetes Attitudes, Wishes, and Needs), DD was reported by 44.6% of participants. Objectives: The purpose of this study was to assess the prevalence and level of DD and its associated factors among adult diabetic patients in South East Nigeria. Methods: The present study was cross-sectional and descriptive. Patients attending the adult diabetes clinic were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…In addition, we found that diabetes duration was higher in the studies about diabetes distress. This is in agreement with a recent study that found an association of diabetes distress with a longer diabetes duration, younger age, use of insulin and T1D [42].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, we found that diabetes duration was higher in the studies about diabetes distress. This is in agreement with a recent study that found an association of diabetes distress with a longer diabetes duration, younger age, use of insulin and T1D [42].…”
Section: Discussionsupporting
confidence: 94%
“…Studies that were done in Bangladesh 39 and Malaysia 13 using the DDS-17 scale showed that almost half of patients with T2DM had DRD. Studies in Ghana 22 and Nigeria 19 reported that 44.7% and 51.9% of patients had high levels of DRD, respectively. This discrepancy between the previously reported DRD magnitude and the current prevalence might result from better family and social support implemented in our societies and patients might have under-rated their level of distress.…”
Section: Discussionmentioning
confidence: 98%
“… 17 , 18 Studies illustrated that younger age, lower level of education, longer duration of diabetes, use of insulin injection, and higher HbA1c were factors strongly associated with higher DRD in the cross-sectional analyses. 19–21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By itself, pharmacologic management does not ensure improvement in long-term patient-oriented outcomes such as the quality of life or all-cause mortality. Additional nonpharmacologic interventions are needed to empower individuals to improve their quality of life [2]. Yet, a majority of these individuals remain nonadherent to lifestyle guidelines [3].…”
Section: Introductionmentioning
confidence: 99%